Functional and structural analysis of a novel splice site HMBS variant in a Chinese AIP patient - Wang, Xiaoqing; Zhang, Huifen; Huang, Huanhuan; Wang, Wenli; Wen, Yuping; Dai, Zhuojin; Huang, Shuling; Zhou, Jingyi; Zhou, Yuqing (Frontiers in Genetics, 2023)
Background: Acute intermittent porphyria (AIP) is a rare metabolic disorder that results from mutations in the gene encoding hydroxymethylbilane synthase (HMBS), an enzyme involved in heme biosynthesis. AIP follows an autosomal dominant inheritance pattern, but most carriers are asymptomatic. The clinical manifestations of AIP include acute attacks of abdominal pain and neuropsychiatric disturbances. The pathogenicity of novel HMBS variants identified in Chinese patients has not been well established. Objective: The article aims to identify the pathogenic mutation in an AIP patient and prove its pathogenicity through in vitro experiments. Methods: A 22-year-old female diagnosed with AIP participated in the study. Variant screening of her HMBS gene was carried out through Sanger sequencing. To ascertain the consequences of the newly discovered variant, we conducted in vitro experimentation targeting HMBS gene expression and enzymatic function. Additionally, protein structure analysis was performed. Cycloheximide treatment and UPF1-specific siRNA knockdown were employed to assess the impact of the mutation on the mechanism of nonsense-mediated mRNA decay (NMD). Results: A novel splice site variant in the HMBS gene (c.648_651+1delCCAGG) was detected in the patient, which caused aberrant mRNA splicing. In vitro experiments demonstrated that this variant significantly decreased the expression of HMBS. Further investigation confirmed that this decrease was due to NMD. Additionally, structural analysis indicated that this variant would destabilize the HMBS protein and impair its catalytic activity. To gain a comprehensive understanding of HMBS mutations in the context of AIP, we conducted a literature search on PubMed using the keywords 'HMBS' and 'Acute intermittent porphyria' from 2013 to 2023. This search yielded 19 clinical case reports written in English, which collectively described 220 HMBS gene mutations worldwide. Conclusion: The study identified and proved the pathogenicity of a novel splice site HMBS variant for the first time. Our results elucidated the pathological mechanism by which this mutation causes AIP through reducing HMBS expression and activity. These findings provide theoretical guidance for the diagnosis, treatment and genetic counseling of AIP patients.